1991
DOI: 10.1021/ja00023a036
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies and modeling of a self-replicating system

Abstract: A close and relevant parallel is the ionization of (the isoelectronic) primary amides. Here too calculations indicate that the 2 isomer (of the anion) is more stable in the gas phase by about 5 kcal/mol.'8 Since the isomeric anions are in equilibrium with the same conjugate acid, this is a direct measure of the difference (1 7) The calculated (>5 kcal/mol) preference of esters for the 2 conformation is also much reduced in solution, as indicated by a measured ("C NMR) value of 1.67 kcal/mol for ethyl formate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(52 citation statements)
references
References 2 publications
4
44
0
1
Order By: Relevance
“…Catalytic antibodies, which were originally reported in 1986, can be characterized as antibodies directed against haptens, which are usually synthetic analogs of the transition states of the chemical reactions to be catalyzed. Reengineering of enzymes has been possible in principle since the advent of genetic engineering, more than two decades ago; a review of Medline entries indicated that studies involving site-directed mutagenesis of enzymes for both reengineering and purely investigatory purposes have produced an average of over 280 papers a year since 1990 in the joumals catalogued by Medline.t At the opposite conceptual end of the field, chemists interested in catalysis have selected aspects of enzyme behavior capable of being mimicked in smaller systems and have succeeded in producing catalysts with a number of enzyme-like features (6)(7)(8)(9)(10)(11)(12). Catalytic RNA or "ribozyme" technology (13,14) represents yet another promising area in biocatalysis, but it is still possible that the catalytic capabilities of ribozymes, which necessarily have smaller chemical and structural repertoires available than proteins and general synthetic constructs, will prove to be limited to acyl transfer and hydrolysis reactions; these are both areas in which catalytic antibodies and RNEs are already highly proficient.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Catalytic antibodies, which were originally reported in 1986, can be characterized as antibodies directed against haptens, which are usually synthetic analogs of the transition states of the chemical reactions to be catalyzed. Reengineering of enzymes has been possible in principle since the advent of genetic engineering, more than two decades ago; a review of Medline entries indicated that studies involving site-directed mutagenesis of enzymes for both reengineering and purely investigatory purposes have produced an average of over 280 papers a year since 1990 in the joumals catalogued by Medline.t At the opposite conceptual end of the field, chemists interested in catalysis have selected aspects of enzyme behavior capable of being mimicked in smaller systems and have succeeded in producing catalysts with a number of enzyme-like features (6)(7)(8)(9)(10)(11)(12). Catalytic RNA or "ribozyme" technology (13,14) represents yet another promising area in biocatalysis, but it is still possible that the catalytic capabilities of ribozymes, which necessarily have smaller chemical and structural repertoires available than proteins and general synthetic constructs, will prove to be limited to acyl transfer and hydrolysis reactions; these are both areas in which catalytic antibodies and RNEs are already highly proficient.…”
mentioning
confidence: 99%
“…Category 3 is not manifestly impossible, but since mechanisms by which the free energy of association is transduced in natural enzymes are poorly understood, it would be astonishing if this effect could be designed and used efficiently in a de novo-designed molecule until further major advances are made in structure prediction and protein dynamics. Category 4 is the feature most readily available to the biocatalyst designer, and the most successful attempts in this field have made free use of contemporary knowledge of both chemical catalysis and the roles of active site residues in enzymes (6)(7)(8)(9)(10)(11)(12)36); however, as mentioned above, our ability to apply this knowledge effectively is severely limited by our failure, for the most part, to deliver appropriate three-dimensional scaffolds for proper placement of the tools of catalysis. Smaller, disordered peptides may contain all the functional groups of enzyme active sites, but even if the peptide is capable of assuming a catalytic conformation, it is conceivable, given the enormous magnitude of shape space accessible to a peptide of even 30 amino acid residues, that the age of the planet would elapse before the desired conformation were to be assumed (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That even much smaller and simpler molecules are capable of exhibiting self-replication, was first shown by Rebek and co-workers for artificial synthetic models ( Figure 1) [10,11].…”
Section: Reviewmentioning
confidence: 87%
“…Although the present system has some phenomenological similarities to autocatalysis, there are important differences. First, templated autocatalysis selects specific molecular products from a sea of reactive possibilities based on their ability to reproduce (15)(16)(17)(18)(19)(20)(21)(22)(23). Traditional autocatalysis involves direct competition of individual molecules.…”
Section: [1] [2]mentioning
confidence: 99%